2009
DOI: 10.26719/2009.15.3.622
|View full text |Cite
|
Sign up to set email alerts
|

Woman abuse and pregnancy outcome among women in Khoram Abad, Islamic Republic of Iran

Abstract: We carried out a descriptive analysis on the pregnancy outcome in 313 pregnant women (153 abused, 160 non-abused). Abuse was statistically significantly correlated with mean weight gain during pregnancy, mean frequency of the prenatal care, prolonged labour (dystocia), premature rupture of membrane, low mean birth weight and mean gestational age at birth. Given the high likelihood that a woman will access health care services during her pregnancy, physicians providing prenatal care are in a strategic position … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 15 publications
3
20
0
Order By: Relevance
“…Seven studies with high methodological quality included outcomes of premature rupture of membranes . Two found an association with undifferentiated IPV, five with physical IPV, and two others with psychological IPV . The risk was between 1.9 and 5.1 times higher in women exposed to physical IPV, 3.2 times higher in women exposed to undifferentiated IPV and between 1.5 and 1.6 times higher in women exposed to psychological IPV.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Seven studies with high methodological quality included outcomes of premature rupture of membranes . Two found an association with undifferentiated IPV, five with physical IPV, and two others with psychological IPV . The risk was between 1.9 and 5.1 times higher in women exposed to physical IPV, 3.2 times higher in women exposed to undifferentiated IPV and between 1.5 and 1.6 times higher in women exposed to psychological IPV.…”
Section: Resultsmentioning
confidence: 99%
“…Forty-one studies (82%, n = 41) were of high methodological quality (indicating low risk of bias) ( Table 2). [18][19][20][21][22][23][24][25][26]28,29,[31][32][33][34][35][36][37][38][39][40][41]43,[46][47][48][49][51][52][53][56][57][58][59][60][61][62][63][65][66][67] Most of the studies with high or moderate risk of bias obtained low scores in sample selection 30,45,50,54,55,64 or comparability. 27,45,50,…”
Section: Methodological Quality Of Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…All 16 studies had examined the relationship between the intermediate determinants of health and preterm birth, but of all the determinants based on the WHO model, only 7 were examined, including anxiety in 3 studies (33)(34)(35), depression in 2 (33,36), violence in 7 (24,(26)(27)(28)32,36), unwanted pregnancy in 2 (29,36), poor health behaviors in 2 (37,38), exposure to secondhand tobacco smoke in 3 (31,36,40), and prenatal care in 2 studies (36,39) (Table 3). Generation of Results As shown in Figure 2, evaluating the relationship between education and preterm birth, Alizadeh et al showed that preterm birth is more common in illiterate compared to educated women.…”
Section: Resultsmentioning
confidence: 99%